2017
DOI: 10.1002/rra.3224
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of silver eels migrating through different types of hydropower turbines in Lithuania

Abstract: Hydropower plants (HPP) are considered to be one of the major threats to the survival of European eels when they migrate downstream along inland water bodies during the early part of their annual journey to the spawning area in the Sargasso Sea. There are 98 HPPs in Lithuania and thousands throughout Europe. Numerous studies describe HPP induced mortality rates among European eels as variable depending on local, environmental, and technical factors. This heterogeneity in effect complicates theoretical extrapol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Larinier () summarized turbine mortalities in different studies and concluded that turbine mortality is a minimum of 10–20% in large low‐head turbines and more than 50% in the smaller turbines used in most small‐scale hydroelectric power plants. Some turbines may even impose a 100% mortality (Dainys, Stakenas, Gorfine, & Lozys, ; Larinier & Travade, ). Mortality rates of eels when passing through turbines are generally higher than for instance for Atlantic salmon ( Salmo salar ) smolts because of greater body lengths (Larinier, ).…”
Section: Discussionmentioning
confidence: 99%
“…Larinier () summarized turbine mortalities in different studies and concluded that turbine mortality is a minimum of 10–20% in large low‐head turbines and more than 50% in the smaller turbines used in most small‐scale hydroelectric power plants. Some turbines may even impose a 100% mortality (Dainys, Stakenas, Gorfine, & Lozys, ; Larinier & Travade, ). Mortality rates of eels when passing through turbines are generally higher than for instance for Atlantic salmon ( Salmo salar ) smolts because of greater body lengths (Larinier, ).…”
Section: Discussionmentioning
confidence: 99%
“…Searching and recurrence behaviour and upstream swimming enhance the chance of finding these alternative routes if they are in the vicinity and have sufficient attraction by cues. Mortality rates can also be reduced when eels are hindered from entering the turbines, for example covering the entrance with racks with narrow bar spacings and at the same time supplying safe bypass routes (Dainys, Stakenas, Gorfine, & Lozys, 2018; Økland et al, 2019; Travade et al, 2010). A large, fine‐mesh trash rack, however, is technically challenging to construct and operate, and could result in fish mortality due to impingement (Calles et al, 2010; Fjeldstad et al, 2018).…”
Section: Implications For Managementmentioning
confidence: 99%
“…Stocks of European eel Anguilla anguilla (l. 1758) and American eel ( Anguilla rostrata LeSueur 1817) have declined over past decades (Bernaś et al ., ; Bruijs & Durif, ; Dainys et al ., ; Dekker, ; EPRI, ; Travade et al ., ). Among a host of causative factors ( e.g ., overfishing, dam construction, habitat loss, etc .)…”
Section: Introductionmentioning
confidence: 99%
“…Despite concerns on the fate of silver eels passing through hydro turbines, published literature is relatively sparse compared with that on emigrating clupeids and salmonids. EPRI's (, ) review and of others (Bernaś et al ., ; Bruijs & Durif, ; Calles, ; Dainys et al ., ; Larinier & Travade, ; Travade et al ., ) indicated that earlier passage studies primarily utilised netting systems to capture turbine‐passed emigrating silver eels. A large amount of variation (mortality of between 15 and 38% at large propeller turbines and 50 to 100% at small turbines for European eel) was noted across sites in these uncontrolled field studies (Bernaś et al ., ; Bruijs & Durif, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation